2021
DOI: 10.1021/acs.est.1c06342
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Nitrogen Species Generated by Gas–Liquid Dielectric Barrier Discharge for Efficient Degradation of Perfluorooctanoic Acid from Water

Abstract: Perfluorooctanoic acid (PFOA) poses a serious threat to the ecological environment and biological health because of its ubiquitous distribution, extreme persistence, and high toxicity. In this study, we designed a novel gas–liquid dielectric barrier discharge (GLDBD) reactor which could efficiently destruct PFOA. PFOA removal efficiencies can be obtained in various water matrices, which were higher than 98.0% within 50 min, with energy yields higher than 114.5 mg·kWh–1. It was confirmed that the reactive speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…Then, C 7 F 15 O • is subdivided into the C 6 F 13 • radical and COF 2 ; COF 2 could rapidly react with water to finally form CO 2 and HF. By this continuous repeating CF 2 -unzipping cycle, the chain scission defluorination process eventually converts PFOA to H 2 O, CO 2 , and HF. , Most importantly, the pathway of Ti 3 C 2 O 2 is the most favorable among the three different models, which also indicates that the O-terminated surface is much more effective than Cl- and F-terminated surfaces.…”
Section: Resultsmentioning
confidence: 96%
“…Then, C 7 F 15 O • is subdivided into the C 6 F 13 • radical and COF 2 ; COF 2 could rapidly react with water to finally form CO 2 and HF. By this continuous repeating CF 2 -unzipping cycle, the chain scission defluorination process eventually converts PFOA to H 2 O, CO 2 , and HF. , Most importantly, the pathway of Ti 3 C 2 O 2 is the most favorable among the three different models, which also indicates that the O-terminated surface is much more effective than Cl- and F-terminated surfaces.…”
Section: Resultsmentioning
confidence: 96%
“…In the absence of R·, Δ G was 693.34 kJ mol –1 , which was consistent with the results of Zhu et al. (694.88 kJ mol –1 ) . Therefore, it was difficult to initiate the degradation of PFOA without R·.…”
Section: Resultsmentioning
confidence: 97%
“…Excitingly, the Cl· mediated generation of C 7 F 15 COO· achieved the lowest Δ G (65.57 kJ mol –1 ), much lower than that of ·OH. It has been reported that SO 4 •– and NO 2 · can degrade PFOA with additional energy input such as light or heat. The DFT calculations showed that the Δ G values for SO 4 •– (93.07 kJ mol –1 ) and NO 2 · (173.10 kJ mol –1 ) were higher than that of Cl·. Furthermore, the Δ G ‡ of a single electron transfer reaction was obtained according to the Marcus theory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ferulic acid, which reacts with ˙NO 2 with a rate constant of 7.4 × 10 8 M −1 s −1 and with ˙OH with a rate constant of approximately 10 10 M −1 s −1 , 57 has been used as a ˙OH and ˙NO 2 scavenger in a handful of studies probing the role of ˙NO 2 in contaminant transformation. 58–60 Flavanone, which acts as a radical scavenger in the human body, has been used as a scavenger in experiments assessing the role of ˙NO, 61 although flavonoids also react with ˙OH. 62 While scavengers can provide evidence for a role of RNS by inhibiting RNS reactions, quantifying the roles of ˙OH and RNS in organic compound transformation requires estimates of steady-state reactive intermediate concentrations.…”
Section: Rns In Sunlit Watersmentioning
confidence: 99%